Ideology, Critique and Surveillance - Heidi Herzogenrath-Amelung (tripleC: Communication, Capitalism & Critique)
The 2013 revelations concerning global surveillance programmes demonstrate in unprecedented clarity the need for Critical Theory of information and communication technologies (ICTs) to address the mechanisms and implications of increasingly global, ubiquitous surveillance. This is all the more urgent because of the dominance of the “surveillance ideology” (the promise of security through surveillance) that supports the political economy of surveillance. This paper asks which theoretical arguments and concepts can be useful for philosophically grounding a critique of this surveillance ideology. It begins by examining how the surveillance ideology works through language and introduces the concept of the ‘ideological packaging’ of ICTs to show how rhetoric surrounding the implementation of surveillance technologies reinforces the surveillance ideology. It then raises the problem of how ideology-critique can work if it relies on language itself and argues that Martin Heidegger’s philosophy can make a useful contribution to existing critical approaches to language.